2009
DOI: 10.1128/jb.01592-08
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Outer Membrane Protein AsmA of Salmonella enterica in the Control of marRAB Expression and Invasion of Epithelial Cells

Abstract: A genetic screen for suppressors of bile sensitivity in DNA adenine methylase (dam) mutants of Salmonella enterica serovar Typhimurium yielded insertions in an uncharacterized locus homologous to the Escherichia coli asmA gene. Disruption of asmA suppressed bile sensitivity also in phoP and wec mutants of S. enterica and increased the MIC of sodium deoxycholate for the parental strain ATCC 14028. Increased levels of marA mRNA were found in asmA, asmA dam, asmA phoP, and asmA wec strains of S. enterica, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…Previous studies have shown that bile sensitivity of S. enterica dam mutants is suppressed by two classes of recessive mutations: (i) in the mismatch repair genes mutH, mutL, and mutS (18) and (ii) in the asmA gene (17). The MIC analyses represented in Table 1 indicated that lack of AsmA suppresses DOC sensitivity in a damX background, while inactivation of the MutHLS system does not.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…Previous studies have shown that bile sensitivity of S. enterica dam mutants is suppressed by two classes of recessive mutations: (i) in the mismatch repair genes mutH, mutL, and mutS (18) and (ii) in the asmA gene (17). The MIC analyses represented in Table 1 indicated that lack of AsmA suppresses DOC sensitivity in a damX background, while inactivation of the MutHLS system does not.…”
mentioning
confidence: 94%
“…This is a relevant difference between dam and damX mutants despite the fact that both mutant types are bile sensitive. Lack of AsmA has previously been shown to activate the Mar regulon, which may in turn activate efflux pumps and other protective devices (17). As a consequence, asmA mutations suppress bile sensitivity in genetic backgrounds as diverse as dam, phoP, and wec (17).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 (ii) Sensitivity to bile in S. enterica dam mutants is suppressed by inactivation of either the MutHLS system or the AsmA protein. 22,23 In S. enterica damX mutants, however, bile sensitivity is suppressed by inactivation of AsmA, but not by inactivation of the MutHLS system, suggesting that the causes of bile sensitivity in dam and damX mutants are different.…”
Section: Expression Of the Damx Genementioning
confidence: 95%